Triphasic Pulses in Cochlear Implant Patients With Facial Nerve Stimulation. Issue 10 (December 2019) - Braun, Katharina; Walker, Kevin; Sürth, Werner; Löwenheim, Hubert; Tropitzsch, Anke
Abstract : Objective: Evaluation of triphasic pulse stimulation in comparison to the traditional biphasic pulse stimulation in cochlear implant (CI) patients with unintended facial nerve costimulation. Study Design: Retrospective case review. Setting: Cochlear Implant Center of a University Department of Otolaryngology, Head and Neck Surgery. Patients: Fifteen CI patients (MED-EL, Innsbruck, Austria) received a triphasic fitting map instead of a biphasic fitting map due to a previous diagnosis of facial nerve stimulation or stimulus induced pain during the years 2014 to 2017. Intervention(s): Application of a triphasic stimulation strategy. Main Outcome Measure(s): Reduction of facial nerve costimulation and speech understanding. Biphasic and triphasic fitting maps were compared to accurately assess the effects of the switch, and hearing tests (monosyllables and sentences in noise tests) were analyzed. Results: Triphasic pulse stimulation showed a significant reduction of unintended side effects and resulted in an observed improved quality of life in most cases. Although there was no significant change in the understanding of speech with CI in all test situations, in many cases, improvement was observed. Conclusions: Triphasic pulse stimulation had a beneficial effect for CI patients with severe, unintended costimulation and should be considered a valuable tool during CI fitting.